Synergy or interference of a H9N2 avian influenza virus with a velogenic Newcastle disease virus in chickens is dose dependent. Issue 5 (3rd September 2017) - Bonfante, Francesco; Cattoli, Giovanni; Leardini, Sofia; Salomoni, Angela; Mazzetto, Eva; Davidson, Irit; Haddas, Ruth; Terregino, Calogero
ABSTRACT: Field observations indicate that the impact of velogenic Newcastle disease virus (vNDV) is more severe in countries with concomitant circulation of low pathogenicity avian influenza virus, as is the case in the Middle East, in particular in Israel, where H9N2 and NDV are endemic. In our study, we evaluated how the exposure of chickens to an H9N2 challenge either favours or interferes with a subsequent vNDV infection and its transmission to sentinels. For this purpose, single vNDV and sequential H9/NDV challenges were performed with increasing doses of vNDV (10 1 –10 6 EID50 ). The H9N2 challenge made birds more susceptible to the vNDV, lowering the minimum dose required to cause an infection, exacerbating the clinical outcome, while delaying the onset of the disease and time of death. Interestingly, the presence and degree of these seemingly contrasting effects were dose-dependent and not mutually exclusive.